Herding, Warfare, and a Culture of Honor: Global Evidence - Yiming Cao; Benjamin Enke; Armin Falk; Paola Giuliano; Nathan Nunn (Institute of Labor Economics (IZA), 2021)
According to the widely known 'culture of honor' hypothesis from social psychology, traditional herding practices are believed to have generated a value system that is conducive to revenge-taking and violence. We test this idea at a global scale using a combination of ethnographic records, historical folklore information, global data on contemporary conflict events, and large-scale surveys. The data show systematic links between traditional herding practices and a culture of honor. First, the culture of pre-industrial societies that relied on animal herding emphasizes violence, punishment, and revenge-taking. Second, contemporary ethnolinguistic groups that historically subsisted more strongly on herding have more frequent and severe conflict today. Third, the contemporary descendants of herders report being more willing to take revenge and punish unfair behavior in the globally representative Global Preferences Survey. In all, the evidence supports the idea that this form of economic subsistence generated a functional psychology that has persisted until today and plays a role in shaping conflict across the globe.
Keywords: N0; Z1; 330; culture of honor; conflict; punishment; revenge